BOOKS ON THE BORDER WAR, 1966–1990 - Jacobs, CJ (Scientia Militaria - South African Journal of Military Studies, 2013)
Review article on the following: De Vries, R. 2013. In the eye of the firestorm; Paarl: Naledi. Scholtz, L. 2013. The SADF in the Border War, 1966–1989. Cape Town: Tafelberg. Bothma, LJ. 2012. Vang ’n Boer. Bloemfontein: Self publication.